The Importance of School Principals' Values towards the Inclusive Education of Disabled Students: Associations between Their Values and Knowledge, Beliefs, Attitudes and Practices - Anastasia Vlachou; Smaragdi S. Tsirantonaki (MDPI AG, 2023)
The current paper presents part of a broader, large-scale study regarding inclusive education and educational leadership in Greece that highlights the decisive role that school principals' values play into shaping inclusive education. Its proposed theoretical model, based on extensive bibliographical research, explores the relationships between values, and knowledge, beliefs, attitudes and practices regarding the education of disabled students, highlighting that school principals' values influence their beliefs and attitudes, and by extension their inclusive practices. Thus, the current paper presents a large-scale research on the proposed theoretical model with a representative sample of Greek primary and secondary education school principals. The data were collected with a composite questionnaire adapted and validated for the Greek context, which was electronically administered to a sample of 582 school principals from 334 primary and 248 secondary schools. The results of a hierarchical multiple regression analysis and a pathway analysis were interpreted based on the strength and direction of the relationships between the examined variables, as well as their significance. The hierarchical multiple regression analysis revealed that school principals' knowledge and beliefs regarding the education of disabled students, and to a lesser extent their values, predicted whether school principals implement practices regarding the education of said students in their school units. However, school principals' values were indeed the strongest predictive factor for their attitudes towards the education of disabled students and along with their knowledge, play a catalytic role in shaping their beliefs, attitudes and by extension, their practices regarding the education of disabled students. The pathway analysis confirmed the schematic representation of the regression relationships between the examined variables which showed that the theoretical model captures the predictive relationships among the variables, identifies potential causal pathways and showcases their decisive role in inclusive educational leadership. In short, the theoretical model demonstrates a very good fit to the research data coming in agreement with the results from both statistical analyses. Thus, it outlines a consistent and coherent outcome, which highlights multiple relationships between the variables, but primarily the multilayered effect of values in the case of inclusive educational leadership.